Perbedaan hasil belajar kimia siswa yang dibelajarkan dengan media kahoot dan media powerpoint pada materilaju reaksi di SMA - Sari, Aisyah Fitria; Pasar Maulim Silitonga (ARKA INSTITUTE, 2022)
This research aims to determine the comparison of student learning outcomes taught using the Kahoot learning media and student learning outcomes taught using the Powerpoint learning media. The population in this study were all students in class XI Science at Al-Hikmah Private High School 2021/2022. The class sample is a saturated sample and the student sample was taken purposively from 25 students from each class who were relatively homogeneous. Based on the results of research using the right-hand t test for one sample group, it was found that the average learning outcomes of students taught using the Kahoot learning media were higher than the minimum completeness criteria. The results of further research using the right-hand t test for two sample groups showed that the average learning outcomes of students who were taught using the Kahoot learning media were higher than the learning outcomes of students who were taught using the Powerpoint learning media. In this research, it was also found that in Kahoot learning, a percentage of students achieved the minimum completeness criteria. So it can be concluded that learning outcomes using Kahoot media and Powerpoint media are higher using Kahoot media on chemical reaction rate material in high school.